Different bonding agents effect on adhesive bond strength: lithium disilicate glass ceramic - Marcos Daniel Septímio LANZA; Walisson Arthuso VASCONCELLOS; Giovani Lana Peixoto de MIRANDA; Rogéli Tibúrcio Ribeiro da Cunha PEIXOTO; Lincoln Dias LANZA (Universidade Estadual Paulista, 2020)
Abstract Introduction The silanization of the ceramic surface prior to applying the adhesive and/or resinous materials plays an important role in bond strength. Nowadays, a new family of adhesive systems has been introduced into the market, aiming to simplify the technique of adhesive procedures during cementation. Objective To investigate the effectiveness of different bonding agents containing silane and primer on Lithium Disilicate Glass Ceramic (LD) surface by shear bond strength tests. Material and method 130 LD ceramic blocks were included in acrylic resin, polished and washed in ultrasound for 10 minutes. The specimens were divided into 2 groups according to surface treatment: Polished Surface (PS); Hydrofluoric Acid 9.5% - 20s (HF). Each group was divided into 5 subgroups (n = 13) according to bonding agent type: metallic primer containing MDP (ZPrimePlus, Bisco Inc); two traditional silanes (MonobondPlus, IvoclarVivadent / Porcelain Prime, Bisco Inc.); mixture of silane and resin (Kerr Silane, Kerr); mixture of silane and universal adhesive (Single-bond Universal, 3M Espe). The specimens were mounted in a standard device for shear testing (UltradentBonding Assembly), cemented with dual resin cement (RelyX UltimateTM, 3M Espe.) and photo-polymerized for 20s. The samples were tested after 24 hours and 3 months of storage in distilled water at ±36 °C. The data were analyzed by 3-Way Anova and Tukey's test (α = 5%). Result Shear bond strength (SBS) was significantly influenced by surface treatment, bonding agent used and storage (p <0.001). Conclusion Adequate adhesive bond strength to Lithium Disilicate Glass Ceramic can be obtained with traditional silanes, combined with HF acid pretreatment surface.